JAK1-dependent transphosphorylation of JAK2 limits the antifibrotic effects of selective JAK2 inhibitors on long-term treatment - Zhang, Yun; Liang, Ruifang; Chen, Chih-Wei; Mallano, Tatjana; Dees, Clara; Distler, Alfiya; Reich, Adam; Bergmann, Christina; Ramming, Andreas; Gelse, Kolja; Mielenz, Dirk; Distler, Oliver; et al. (Annals of the Rheumatic Diseases, 2017)
Janus kinase 2 (JAK2) has recently been described as a novel downstream mediator of the pro-fibrotic effects of transforming growth factor-?. Although JAK2 inhibitors are in clinical use for myelodysplastic syndromes, patients often rapidly develop resistance. Tumour cells can escape the therapeutic effects of selective JAK2 inhibitors by mutation-independent transactivation of JAK2 by JAK1. Here, we used selective JAK2 inhibition as a model to test the hypothesis that chronic treatment may provoke resistance by facilitating non-physiological signalling pathways in fibroblasts.The antifibrotic effects of long-term treatment with selective JAK2 inhibitors and reactivation of JAK2 signalling by JAK1-dependent transphosphorylation was analysed in cultured fibroblasts and experimental dermal and pulmonary fibrosis. Combined JAK1/JAK2 inhibition and co-treatment with an HSP90 inhibitor were evaluated as strategies to overcome resistance.The antifibrotic effects of selective JAK2 inhibitors on fibroblasts decreased with prolonged treatment as JAK2 signalling was reactivated by JAK1-dependent transphosphorylation of JAK2. This reactivation could be prevented by HSP90 inhibition, which destabilised JAK2 protein, or with combined JAK1/JAK2 inhibitors. Treatment with combined JAK1/JAK2 inhibitors or with JAK2 inhibitors in combination with HSP90 inhibitors was more effective than monotherapy with JAK2 inhibitors in bleomycin-induced pulmonary fibrosis and in adTBR-induced dermal fibrosis.Fibroblasts can develop resistance to chronic treatment with JAK2 inhibitors by induction of non-physiological JAK1-dependent transactivation of JAK2 and that inhibition of this compensatory signalling pathway, for example, by co-inhibition of JAK1 or HSP90 is important to maintain the antifibrotic effects of JAK2 inhibition with long-term treatment.
EVALuna2:13270